Systems capacity expansion planning: Novel approach for environmental and energy policy change analysis. (November 2016) - Arancibia, Ada Liz; Marques, Guilherme Fernandes; Bulhões Mendes, Carlos André
Abstract: Planning for power systems generation expansion follows environmental policies incorporating technologies based on renewables to reduce CO2 emissions. These policies are susceptible to unpredictable changes, given dynamic economic and political contexts. This paper analyzes the impact of changes in energy policies, motivated by different environmental objectives. The analysis is done through a novel approach coupling Dynamic Programming and Multi-objective programming to generate several energy policy scenarios and their trade-offs, representing plausible policy changes in the different stages of the planning horizon. The results indicate a clear Pareto front and that energy policy scenarios with abrupt changes should be avoided in favor of scenarios with gradual changes. "Greener" energy policies in a given planning stage are not necessarily the best ones considering the full planning horizon, considering the unfolding impacts of current decisions into the future. The approach is useful in improving planners' future vision from myopic into a perspicacious one. Highlights: Future energy policy decisions are highly uncertain and subject to change. Facing uncertainty requires knowledge of economic and environmental tradeoffs. Integrating MOLP to optimize DP sub problems allows tradeoffs identification. Energy policy changes along planning horizon is important in capacity expansion. Policies to reduce CO2 emissions tend to perform better if implemented gradually.